Christian Defence of Free Will in Debate with Muslims in the Early Islamic Period. (July 2019) - Beaumont, Mark
Two Christian theologians writing in Arabic in the early ninth century argued that God had created humanity to freely choose good or evil actions, a belief shared universally by previous Christian writers in Greek and Syriac no matter the denomination they came from. They were debating with Muslim intellectuals who held that God created all human actions before they were acquired by humans, so that God had already decided which actions a particular human being would choose, whether good or evil. Theodore Abū Qurra and ʿAmmār al-Baṣrī developed dialogues with determinist Muslims in the hope that they might influence these determinist Muslims to adopt earlier Muslim beliefs that the Qurʾan taught that God would judge humans for the choices that they freely made for good or evil. However, the trend towards determinism was so strong that by the end of the ninth century the mainstream Sunni view would be that God decreed all human actions before they were acquired by humans.